Depletion of ALMS1 affects TGF-β signalling pathway and downstream processes such as cell migration and adhesion capacity - Bea-Mascato, Brais; Neira-Goyanes, Elena; Iglesias-Rodríguez, Antía; Valverde, Diana (Frontiers in Molecular Biosciences, 2022)
Background: ALMS1 is a ubiquitous gene associated with Alström syndrome (ALMS). The main symptoms of ALMS affect multiple organs and tissues, generating at last, multi-organic fibrosis in the lungs, kidneys and liver. TGF-β is one of the main pathways implicated in fibrosis, controlling the cell cycle, apoptosis, cell migration, cell adhesion and epithelial-mesenchymal transition (EMT). Nevertheless, the role of ALMS1 gene in fibrosis generation and other implicated processes such as cell migration or cell adhesion via the TGF- β pathway has not been elucidated yet. Methods: Initially, we evaluated how depletion of ALMS1 affects different processes like apoptosis, cell cycle and mitochondrial activity. Then, we performed proteomic profiling with TGF-β stimuli in HeLa ALMS1 -/- cells and validated the results by examining different EMT biomarkers using qPCR. The expression of these EMT biomarkers was validated in hTERT-BJ-5ta. Finally, we also evaluated the SMAD3 and SMAD2 phosphorylation in BJ-5ta model and its cell migration capacity. Results: Depletion of ALMS1 generated apoptosis resistance to thapsigargin (THAP) and C2-Ceramide (C2-C), and G2/M cell cycle arrest in HeLa cells. For mitochondrial activity, results did not show significant differences between ALMS1 +/+ and ALMS1 -/-. Proteomic results showed inhibition of downstream pathways regulated by TGF-β. The protein-coding genes (PCG) were associated with processes like focal adhesion or cell-substrate adherens junction in HeLa. SNAI1 showed an opposite pattern to what would be expected when activating the EMT in HeLa and BJ-5ta. Finally, in BJ-5ta model a reduced activation of SMAD3 but not SMAD2 were also observed. In HeLa models no alterations in the canonical TGF-β pathway were observed but both cell lines showed a reduction in migration capacity. Conclusion: ALMS1 has a role in controlling the cell cycle and the apoptosis processes. Moreover, the depletion of ALMS1 affects the signal transduction through the TGF-β and other processes like the cell migration and adhesion capacity.